The Washington manual of echocardiography - Rasalingam, Ravi; Makan, Majesh; Pérez, Julio E. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2013)
"The Washington Manual of Echocardiography contains essential and relevant information for trainees. It has been prepared by cardiology fellows, with the trainees' perspective in mind, and supervised and edited by faculty from the Washington University School of Medicine. The Washington Manual of Echocardiography provides quick insight into the interpretation of echocardiographic images, understanding the basic echocardiographic and Doppler physiology, and assisting with the technical aspects of transducing an echocardiographic exam. The Washington Manual of Echocardiogrpahy is geared toward cardiology fellows, emergency department physicians, and internal medicine residents interested in cardiology. This book is comprehensive enough to carry trainees through the echo rotation as well as concise and accessible at 3 a.m., when trainees are trying to appropriately diagnose important pathologies. It provides easily digestible knowledge and pearls from experienced echocardiologists and sonographers. Features Include: Easy-to-navigate sections on valvular heart disease, cardiomyopathies, congenital anomalies and trans-esophageal echocardiography, Image-heavy pocket book to enhance visual learning, Early emphasis on pearls and techniques on how to transduce an exam and get the optimal images. Succinct yet comprehensive information on key areas of echocardiography and Doppler techniques"--Provided by publisher.